O componente curricular Filosofia no Ensino Médio do Estado de São Paulo a partir das vozes dos alunos - Silva, Marcos da Silva e (2015)
This research intends to discuss the presence of curricular component Philosophy in high school from the voice of student, student of the Public School in the State of Sao Paulo. The research seeks to enhance and open up new avenues for understanding the meaning and scope of this discipline in training and in the life of this student. The Law no. 11.684/2008, amending art. 36 of the Law 9.394 of 20 December 1996 laying down the Principles and Guidelines for national education, to include the Philosophy and Sociology disciplines as mandatory in the curricula of the school. This law provides for mandatory Philosophy as a curricular component. The locus of the research was the public network of São Paulo state education, the subjects were the same students ears at two different times by analyzing their experience from the Philosophy classes. Along the way, the methodological approach was qualitative, with the field of research five public schools in the said network. The student voice was heard through questionnaires that were applied in the 1st year of high school at the end of the school year 2012 and in the 3rd series of the end of the school year 2014. It sought to answer a central question: "What do students think about the curricular component of philosophy"? It was observed that the student values the curricular component Philosophy